Design and analysis of pneumatic based automatic unwind splicing on a rotogravure machine - Rahmadhi, Arif; Sumbodo, Wirawan; Saputro, Danang Dwi; Musyono, Ari Dwi Nur Indriawan; Setiadi, Rizki (Universitas Negeri Semarang, 2024)
The aim of this design is to obtain a design for the tension control system and the automatic system, which are the two mechanisms in the unwind, accompanied by an estimate of the design costs. The design process was carried out using the French method. This method is often used for new products or still has few competitors, with the advantage of being able to facilitate the selection of product concept variants efficiently when designing products that have many limitations in terms of variants. Based on the validation results, the second concept design used is a tension measurement mechanism using a load cell and speed regulation using a magnetic powder brake. The results of numerical calculations show that the maximum rotation torque value of the printed material is 13.6 Nm, the maximum speed is 628.24 rpm, and the maximum stress value measured is 206.122 N. Based on the validation results, the second concept design is a movement mechanism that uses four pneumatic cylinders to move the frame and cutter. The results of numerical calculations show that the time required to cut the material is 0.24 seconds, and the time required to return to its original position is 2.25 seconds. The amount of air required for one cutting cycle is 37.83 ×10-6 m3/s. The estimated cost of designing the overall unwind unit based on the components used is IDR. 74,873,625.